Phosphoproteomic studies in Arabidopsis and tobacco male gametophytes. (20th March 2014) - Fíla, Jan; Čapková, Věra; Honys, David
Abstract : Mature pollen represents an extremely resistant quiescent structure surrounded by a tough cell wall. After its hydration on stigma papillary cells, pollen tube growth starts rapidly. Massive metabolic changes are likely to be accompanied by changes in protein phosphorylation. Protein phosphorylation belongs among the most rapid post-translational modifications. To date, only Arabidopsis thaliana and tobacco ( Nicotiana tabacum ) mature pollen have been subjected to phosphoproteomic studies in order to identify the phosphoproteins present. In the present mini-review, Arabidopsis and tobacco datasets were compared with each other. The representation of the O-phosphorylated amino acids was compared between these two datasets, and the putative pollen-specific or pollen-abundant phosphopeptides were highlighted. Finally, the phosphorylation sites common for both Arabidopsis and tobacco phosphoproteins are listed as well as the phosphorylation motifs identified.